Novel heteroleptic Ru(ii) complexes: synthesis, characterization and application in dye-sensitized solar cells. Issue 12 (17th February 2015) - Marotta, Gabriele; Kumar, Ch. Pavan; Lobello, Maria Grazia; Cavazzini, Francesca; Salvatori, Paolo; Ganesh, Koyyada; Nazeeruddin, Mohammad Khaja; Chandrasekharam, Malapaka; De Angelis, Filippo
Abstract : Photovoltaic efficiencies of 6–8%, comparable with N719, were obtained with six novel Ru(ii ) heteroleptic dyes. Abstract : Six new heteroleptic Ru(ii ) complexes (MC118, MC120–123 andMC126 ), of general formula Ru(L1)(L2)(NCS)2, where L1 and L2 are respectively dicarboxylated and π-conjugated functionalized (dissymmetric) bipyridine ligands, were designed, synthesized and applied as sensitizers in dye-sensitized solar cells. These complexes were characterized both experimentally and theoretically, showing promising optical properties, with higher extinction coefficients compared to the prototypical N719 dye. When employed in working devices, in combination with a liquid I − /I3 − redox electrolyte, the investigated sensitizers have shown power conversion efficiencies between 6.0 and 8.0%, comparable with the reference N719 dye tested under similar fabrication and evaluation conditions.